The social relationship of contemporary residants in Iranian Housing - Mohsen Asadi; Tahir .M.M (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2012)
Iranian Islamic traditional houses have changed fast in recent decades. These changes have had influence on social lifestyle, behavior to relationship of people in Iran and architecture in traditional housing. The traditional architecture of Iranian houses for instance used to include a courtyard surrounded by rooms which controlled privacy, movement and separated people in different situations. In contemporary housing, however, this cultural behavior is lost. Iranian traditional housing, according to reflect the culture, people‟s beliefs and religion; they had harmony in lifestyle and a kind of relationship among spaces of a house. In contemporary house design, without attention to culture and habits of residents, are omitted most of the time. The new apartments are very culturally limited for their residents. This paper concludes that there is a connection between the culture, habits and inhabitants‟ beliefs with the kind of house design (architecture). As a result, in this research it is attempted to analyze some examples, by showing the problems in suitable related to cultural behavior. In addition, it tried to expand that problems in relationship between of residents can appear in very sequences of a house, which of course, is shown in all examples. Besides solving privacy problems, some changes in residential buildings complexes, include, space, and entrance area were done to improve the spatial arrangement of the Muslims‟ house or apartment. The main point is showing the different problems of a house based on the required culture and identity of Iranian dwellers.